Cointegration and Regime-Switching Risk Premia in the U.S. Term Structure of Interest Rates - Peter Tillmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
To date the cointegrating properties and the regime-switching behavior of the term structure are two separate strands of the literature. This paper integrates these lines of research and introduces regime shifts into a cointegrated VAR model. We argue that the short run dynamics of the cointegrated model are likely to shift across regimes while the equilibrium relation implied by the expectations hypothesis of the term structure is robust to regime shifts. A Markov-switching VECM approach for U.S. data outperforms a linear VECM. Moreover, the regime shifts in the risk premium and the equilibrium adjustment reflect shifts in monetary policy.
Keywords: E52; E43; 330; term structure; expectations hypothesis; cointegration; Markov-switching; monetary policy; Zinsstruktur; Zinsstrukturtheorie; Risikoprämie; Kointegration; VAR-Modell; Schätzung; Vereinigte Staaten; Markov switching